Idārah Tanfîdz Manhāj Ta’lîm Al Lughah Al ‘Arabiyyah Fî Al Madrasah Al ‘Āliyah Al Namûdzajiyyah Zainul Hasan Genggong Probolinggo - Shobirin, Shobirin; Abidin, Munirul; Syuhadak, Syuhadak (STIQ Amuntai, 2024)
The curriculum is of the utmost importance. It offers a basic structure that directs the process of learning. It is essential that the curriculum be applied accurately and successfully. Ensuring that learning objectives are satisfied and content is successfully communicated to students is ensured by a robust curriculum implementation. The following are the objectives of this research: 1. The purpose of this study is to identify and characterise the Arabic curriculum implementation management methodology used at Probolinggo's Zainul Hasan Genggong methodology High School. The success of the Arabic curriculum implementation management strategy in helping pupils acquire the language will next be examined. Lastly, it will offer suggestions for enhancement based on the research findings to raise the standard of management for the execution of the Arabic curriculum at Zainul Hasan Genggong Model High School in in Probolinggo.This study uses a qualitative descriptive methodology, gathering information via documentation, interviews, and observation.The study's findings unequivocally showed that the curriculum was successfully implemented and backed by a strong human resource base, cutting-edge teaching strategies, and infrastructure. Leadership dedication, teaching team collaboration, the availability of learning materials, motivation, and student involvement are factors that impact how well a curriculum is implemented. Two of the challenges are different student aptitude levels and scheduling limits. The study suggested hiring more qualified teachers, upgrading the facilities and infrastructure, and utilising information technology that is pertinent to learning Arabic.